An overview of the environmental, economic, and material developments of the solar and wind sources coupled with the energy storage systems. (2nd May 2017) - Balali, Mohammad Hasan; Nouri, Narjes; Omrani, Emad; Nasiri, Adel; Otieno, Wilkistar
Summary: There is a constant growth in energy consumption and consequently energy generation around the world. During the recent decades, renewable energy sources took heed of scientists and policy makers as a remedy for substituting traditional sources. Wind and photovoltaic (PV) are the least reliable sources because of their dependence on wind speed and irradiance and therefore their intermittent nature. Energy storage systems are usually coupled with these sources to increase the reliability of the hybrid system. Environmental effects are one of the biggest concerns associated with the renewable energy sources. This study summarizes the last and most important environmental and economic analysis of a grid‐connected hybrid network consisting of wind turbine, PV panels, and energy storage systems. Focusing on environmental aspects, this paper reviews land efficiency, shaded analysis of wind turbines and PV panels, greenhouse gas emission, wastes of wind turbine and PV panels' components, fossil fuel consumption, wildlife, sensitive ecosystems, health benefits, and so on. A cost analysis of the energy generated by a hybrid system has been discussed. Furthermore, this study reviews the latest technologies for materials that have been used for solar PV manufacturing. This paper can help to make a right decision considering all aspects of installing a hybrid system. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A review of the latest environmental and economic analysis of a hybrid renewable energy network coupled with energy storage systems. A review of the latest material that have been used in solar PV production. This study can be a used as a reliable source for researchers, scientists, policy makers, and engineers to make the right decision.